The Freestyle Battles as an Exercise in Linguistic Creativity: Linguistic Analysis of the Use of Rhetorical Figures - Salcedo Rementerio, Jesús Manuel (2021)
This study shows that the practice of freestyle battles exercises linguistic creativity. Therefore, it proposes that the rhetorical figures used in verbal battles are a sample of the linguistic creativity that rappers present as speakers of a language. Methodologically, he compiles and analyzes the rhetorical resources of Hispanic rappers. The article concludes that freestyle battles promote linguistic creativity and its development should not be stigmatized.